Moore-paradoxical belief, conscious belief and the epistemic Ramsey test - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2012)
Chalmers and Hájek (2007) argue that on an epistemic reading—one that seems reasonable—of Ramsey’s test for the acceptability of conditionals, the test is faulty. They argue for the claim that applying the test to each of certain pair of conditionals requires one to think that one is omniscient or infallible, unless one forms irrational Moore-paradoxical beliefs. I show that this claim is false. The epistemic Ramsey test is indeed faulty. Applying it requires that one think of anyone as omniscient and if one is rational, to think of anyone as infallible-if-rational. But this is not because of Moore-paradoxical beliefs. Rather it is because applying the test requires a certain supposition about conscious belief. It is important to understand the nature of this supposition.